Green supply chain management and the circular economy: Reviewing theory for advancement of both fields. Issue 8 (3rd September 2018) - Liu, Junjun; Feng, Yunting; Zhu, Qinghua; Sarkis, Joseph
Abstract : Purpose: Green supply chain management (GSCM) and the circular economy (CE) overlap but also differ. The purpose of this paper is to clarify linkages between these two concepts. It identifies mutual theory applications used to study GSCM and CE. Design/methodology/approach: A systematic literature review is conducted to identify theories from GSCM and CE studies. A critical analysis explores the theories that can provide mutual applications between GSCM and CE fields. Propositions are developed. Findings: In all, 12 theories are applied in both GSCM and CE studies. Several theories are only applied in GSCM studies, but can help to advance CE study. These theories include complexity, transaction cost economics, agency, and information theories. Each of the eight theories only applied to CE can potentially advance GSCM study. Research limitations/implications: The findings contribute to further theory development for both GSCM and CE study. A methodological review can advance theoretical development and cross-pollination in both fields. Originality/value: This work is the first study to explicitly explore linkages of GSCM and CE from a theoretical perspective.